Deaths from acute abdominal conditions and geographical access to surgical care in India: a nationally representative spatial analysis - Anna J Dare, PhD; Joshua S Ng-Kamstra, MD; Jayadeep Patra, PhD; Sze Hang Fu, MSA; Peter S Rodriguez, MSA; Marvin Hsiao, PhD; Raju M Jotkar, MD; J S Thakur, MD; Jay Sheth, MD; Prof. Prabhat Jha, DPhil (Elsevier, 2015)
Background: Few population-based studies quantify mortality from surgical conditions and relate mortality to access to surgical care in low-income and middle-income countries. Methods: We linked deaths from acute abdominal conditions within a nationally representative, population-based mortality survey of 1·1 million households in India to nationally representative facility data. We calculated total and age-standardised death rates for acute abdominal conditions. Using 4064 postal codes, we undertook a spatial clustering analysis to compare geographical access to well-resourced government district hospitals (24 h surgical and anaesthesia services, blood bank, critical care beds, basic laboratory, and radiology) in high-mortality or low-mortality clusters from acute abdominal conditions. Findings: 923 (1·1%) of 86 806 study deaths at ages 0-69 years were identified as deaths from acute abdominal conditions, corresponding to 72 000 deaths nationally in 2010 in India. Most deaths occurred at home (71%) and in rural areas (87%). Compared with 567 low-mortality geographical clusters, the 393 high-mortality clusters had a nine times higher age-standardised acute abdominal mortality rate and significantly greater distance to a well-resourced hospital. The odds ratio (OR) of being a high-mortality cluster was 4·4 (99% CI 3·2-6·0) for living 50 km or more from well-resourced district hospitals (rising to an OR of 16·1 [95% CI 7·9-32·8] for >100 km). No such relation was seen for deaths from non-acute surgical conditions (ie, oral, breast, and uterine cancer). Interpretation: Improvements in human and physical resources at existing government hospitals are needed to reduce deaths from acute abdominal conditions in India. Full access to well-resourced hospitals within 50 km by all of India's population could have avoided about 50 000 deaths from acute abdominal conditions, and probably more from other emergency surgical conditions. Funding: Bill & Melinda Gates Foundation, Dalla Lana School of Public Health, Canadian Institute of Health Research.